Disparitas Pertanggungjawaban Pidana dalam Korupsi Perjalanan Dinas DPRD Kota Bitung: Analisis Equality Before The Law dan Penyertaan: Studi Putusan Pengadilan Negeri Manado Nomor 48/Pid.Sus-TPK/2025/PN Mnd - Hendro Arifinto Ticoalu; Roy Marthen Moonti (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
The corruption case concerning official travel expenditures of the Bitung City Regional House of Representatives raises a fundamental question regarding the boundary between justifiable differentiation in criminal responsibility and law-enforcement disparity that violates equality before the law. In District Court of Manado Decision Number 48/Pid.Sus-TPK/2025/PN Mnd, six persons were prosecuted, while the audit referred to in the proceedings associated the irregularities with a broader group of official travelers. This study examines the disparity through the principles of equality before the law and criminal participation. It employs normative legal research using statutory, case, and conceptual approaches. Legal materials are analyzed prescriptively by identifying legally relevant facts, mapping individual roles, testing comparability, and evaluating the justification for differential prosecutorial treatment. The study finds that the numerical gap between persons mentioned in an audit and defendants brought to trial constitutes only a prima facie indication of disparity; it does not automatically establish discrimination. A violation of equality arises only when materially comparable persons considering conduct, culpability, benefit, authority, causal contribution, and evidentiary strength receive different treatment without an objective and lawful justification. Participation doctrine requires individualized attribution and rejects collective punishment based solely on administrative proximity. Because judges are confined by the indictment, the main point of scrutiny lies in investigation and prosecution. The article proposes a three-stage framework comprising a comparability test, a justification test, and an accountability-and-follow-up test for assessing disparities in collective corruption cases.